Case Report: Cariprazine in a Patient With Schizophrenia, Substance Abuse, and Cognitive Dysfunction - Rodriguez Cruz, Jose; Sahlsten Schölin, Johan; Hjorth, Stephan (Frontiers in Psychiatry, 2021)
This case report describes a 30-year old male diagnosed with schizophrenia at the age of 23, and with a long history of drug abuse. He had previously received a wide range of antipsychotic drug treatment regimens, all with some degree of effect, but never with complete symptom relief. He was also suffering from persistent cognitive and negative symptoms. At the time of admission in our clinic, he was on Quetiapine (QUE) and Haloperidol (HAL). It was therefore decided to substitute HAL for Cariprazine (CAR) – an agent with a novel pharmacological and clinical profile – in the hope of gaining increased efficacy, particularly in the cognitive and negative symptom domains. Within 3 weeks of the switch from HAL to CAR the patient clearly improved, and notably so in the aforementioned symptom areas. A number of subsequent adjustments of antipsychotic dosages and adjunct medications during the ensuing months resulted in an apparently more stable alleviation of positive as well as negative and cognitive symptoms, including markedly improved personal and social capabilities. Interestingly, some time after initiating CAR treatment the patient also reported that from being a heavy smoker (60 cig/d) he had cut down and eventually ceased smoking entirely; furthermore, he has remained clean of other substance abuse since his first admission in 2020. The joint treatment with CAR in combination with QUE thus seems to have improved the patient’s cognitive functioning as well as possibly his susceptibility to substance abuse.